THE IMPORTANCE OF PEDAGOGICAL PRACTICE IN PROFESSIONAL TEACHER TRAINING - Bayramova Fəridə Məhər qızı (Progress in Science, 2025)
The article highlights the indispensable role of pedagogical practice in shaping students into professional teachers. The internship phase enables students to combine theoretical knowledge with practical activities, fostering skills such as classroom management, communication with students and parents, teamwork, and creative thinking. It also points to challenges such as the quality of internship placements, lack of social preparedness, the limited role of mentoring teachers, and issues in the systematization of pedagogical practice